2012
DOI: 10.1210/jc.2011-2735
|View full text |Cite
|
Sign up to set email alerts
|

Serum TSH and Risk of Papillary Thyroid Cancer in Nodular Thyroid Disease

Abstract: TSH plays a key role in the development of clinically detectable thyroid cancer, and LT4 treatment reduces the risk of thyroid malignancy in patients with nodular thyroid disease. According to the guidelines of the main scientific societies, LT4 therapy is not currently recommended for the treatment of patients with nodular goiter. Even if the available data are not sufficient to advise LT4 treatment in all patients with nodular goiter with the aim of reducing the risk of papillary thyroid carcinoma, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 104 publications
12
120
5
1
Order By: Relevance
“…were more frequent in Non-Inc-microPTC (18/67, 26.9%), than in Inc-microPTC (11/92, 11.9%). It has been shown that in patients with nodular thyroid disease, the risk of clinically detected papillary thyroid cancer increases with increasing concentrations of TSH (26) and, in a mouse animal model with a thyroid-specific knock-in of oncogenic Braf, serum TSH was shown to play a key role in the development of papillary thyroid carcinoma (39). Results obtained in the present series of patients confirm our previous data (27), TSH levels being significantly higher in macroPTC with respect to benign nodular disease.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…were more frequent in Non-Inc-microPTC (18/67, 26.9%), than in Inc-microPTC (11/92, 11.9%). It has been shown that in patients with nodular thyroid disease, the risk of clinically detected papillary thyroid cancer increases with increasing concentrations of TSH (26) and, in a mouse animal model with a thyroid-specific knock-in of oncogenic Braf, serum TSH was shown to play a key role in the development of papillary thyroid carcinoma (39). Results obtained in the present series of patients confirm our previous data (27), TSH levels being significantly higher in macroPTC with respect to benign nodular disease.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In the last few years it has been reported that, in patients with nodular thyroid disease, the risk of thyroid malignancy increases with increasing concentrations of serum thyroid stimulating hormone (TSH) and, even within normal ranges, higher serum TSH levels are associated with a higher frequency and a more advanced stage of thyroid cancer (26). Furthermore, it has been shown that thyroid diseases, that affect thyroid function influencing pituitary secretion of TSH, are associated with a different risk of PTC, with the likelihood of thyroid malignancy reduced when TSH is lower, as in nodular goiter with thyroid autonomy (27) and increased when TSH is higher, as in nodular Hashimoto's thyroiditis (28).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin may also affect deiodinases, activating the T 4 to T 3 conversion (Zimmermann-Belsing et al 2003, Reinehr 2010. In addition to the association between TSH and BMI, there is a clinical association between higher serum TSH levels and an increased risk of malignancy in human thyroid nodules (Fiore & Vitti 2012) and advanced stage of the disease (McLeod et al 2013). As TSH is the major stimulator of thyrocyte proliferation, this hormone could be directly involved in thyroid carcinogenesis in obese subjects (Hard 1998).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…To date, several factors, such as very young and very old age, history of ionizing radiation or head and neck beam radiation in their youth, family history of thyroid cancer, fixed lesion, vocal cord paralysis, and rapid growth, are considered to be risk predictors of malignancy [9,10]. In recent years, a slightly elevated preoperative serum TSH concentration has been reported to be a potential predictor in several studies [11].…”
mentioning
confidence: 99%